Identify the Appropriate Key Performance Indicators for Evaluating the Performance of Construction Companies in Iraq - S. Tofan, Ali; K. Breesam, Hatem (International Journal of Engineering and Technology, 2018)
After 2003, Iraqi market has been opened in front of the world. Many of international companies have entered to the Iraqi construction market. This has led to high competition between construction companies, especially the governmental companies under the Ministry of Construction and Housing. Competition has put a strong pressure on the construction companies to continuously improve their performance. There has been a lot of research for measuring performance at the project's level, but there is a clear lack of research on the performance measurement at the companies' level. The current method of performance evaluation is relying solely on financial indicators, which cannot be the only factor for evaluating performance. Other indicators such as customer's satisfaction, work efficiency, effective planning, etc. have become of great importance to the company success. The research aims are to identify the appropriate set of key performance indicators to measure the performance of construction companies in Iraq. A questionnaire forms have been distributed which includes main performance indicators that derived from the previous studies which affect the construction companies. in conclusion, 10 KPIs selected for the construction companies that can be the start point to make a comprehensive framework for the construction companies in Iraq.Â Â